PEMETAAN ALIRAN DAN CEKUNGAN AIR TANAH MENGGUNAKAN METODE INTERPOLASI KRIGING DI PESISIR KABUPATEN GARUT, JAWA BARAT - sulastri1, ai (JURNAL GEOGRAFI, 2024)
A groundwater basin is an area bounded by hydrogeologic boundaries, where groundwater recharge, flow and discharge processes take place, which is a process of hydrogeologic events. Information on its distribution and availability is important for sustainable utilization planning. This study aims to map groundwater flow and basin in Garut Coastal Area, West Java, using Kriging interpolation method. Data were obtained from field surveys at 66 well points in 10 Areas of Interest (AOI). This method was used to interpolate hydrogeological data to produce an accurate visualization of the distribution of water flow and groundwater basins in the region. Hydrogeological data was collected from various sources, including boreholes and field measurements. The results show variations in groundwater depth between 0.91-41.91 meters with shallow water patterns found in several sub-districts in the southern region. The mapping information can help the management and planning of groundwater utilization as well as the development of the coastal area of Garut Regency. Keywords: Groundwater Basin; Hydrogeology; Kriging